Exogenous ochronosis after prolonged use of topical hydroquinone (2%) in a 50-year-old Indian female - Vijay Gandhi; Prashant Verma; Geetanjali Naik (Wolters Kluwer Medknow Publications, 2012)
Ochronosis is a rare disease characterized by speckled and diffuse pigmentation symmetrically over the face, neck, and photo-exposed areas. It is characterized histologically by banana-shaped ochre-colored deposits in the dermis. It can present in exogenous or endogenous form. We report a case of exogenous ochronosis in a 50-year-old Indian woman after prolonged use of topical hydroquinone which is a rare complication with a commonly used drug which is available over the counter.